2011
DOI: 10.1348/147608310x526511
|View full text |Cite
|
Sign up to set email alerts
|

Fears of compassion: Development of three self‐report measures

Abstract: This study suggests the importance of exploring how and why some people may actively resist engaging in compassionate experiences or behaviours and be fearful of affiliative emotions in general. This has important implications for therapeutic interventions and the therapeutic relationship because affiliative emotions are major regulators of threat-based emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

42
773
1
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 699 publications
(829 citation statements)
references
References 51 publications
(96 reference statements)
42
773
1
13
Order By: Relevance
“…Costa & Pinto Gouveia, 2011; Gilbert et al, 2011; Neff, 2003; Raes, 2010; Roemer et al, 2009; van Dam et al, 2011), and (posttraumatic) stress (e.g. Costa & Pinto Gouveia, 2011; Dahm et al, 2015; Gilbert et al, 2011; Hiraoka et al, 2015; Raque-Bogdan, Ericson, Jackson, Martin, & Bryan, 2011; Thompson & Waltz, 2008). Self-compassion is defined as the tendency to be open to one’s own pain and suffering, to experience feelings of kindness toward oneself, to recognize that one’s experience is part of a common human experience, and to take an understanding, non-judgmental attitude toward one’s failures and inadequacies (Neff, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Costa & Pinto Gouveia, 2011; Gilbert et al, 2011; Neff, 2003; Raes, 2010; Roemer et al, 2009; van Dam et al, 2011), and (posttraumatic) stress (e.g. Costa & Pinto Gouveia, 2011; Dahm et al, 2015; Gilbert et al, 2011; Hiraoka et al, 2015; Raque-Bogdan, Ericson, Jackson, Martin, & Bryan, 2011; Thompson & Waltz, 2008). Self-compassion is defined as the tendency to be open to one’s own pain and suffering, to experience feelings of kindness toward oneself, to recognize that one’s experience is part of a common human experience, and to take an understanding, non-judgmental attitude toward one’s failures and inadequacies (Neff, 2003).…”
mentioning
confidence: 99%
“…Costa & Pinto Gouveia, 2011; Gilbert, McEwan, Matos, & Rivis, 2011; Kuyken et al, 2010; Neff, Pisitsungkagarn, & Hseih, 2008; Raes, 2010, 2011; Roemer et al, 2009; van Dam, Sheppard, Forsyth, & Earleywine, 2011), anxiety (e.g. Costa & Pinto Gouveia, 2011; Gilbert et al, 2011; Neff, 2003; Raes, 2010; Roemer et al, 2009; van Dam et al, 2011), and (posttraumatic) stress (e.g. Costa & Pinto Gouveia, 2011; Dahm et al, 2015; Gilbert et al, 2011; Hiraoka et al, 2015; Raque-Bogdan, Ericson, Jackson, Martin, & Bryan, 2011; Thompson & Waltz, 2008).…”
mentioning
confidence: 99%
“…Gilbert et al (2010) reported McLaughlin et als' (2003) findings that some individuals feel that if one is compassionate toward another he/she will be taken advantage of. We may hypothesize that individuals who have high levels of SDO also have a high Fear of Compassion for Others because they discriminate against outgroup members more than those who have low levels of SDO (Pratto et al 1994) and exhibit uncompassionate behaviors to out-group members (Gilbert et al 2010). SDO Theory would expect those who score high on measures of SDO to score higher on Fear of Compassion for Others given the potentially attenuating effects of compassion on social hierarchies.…”
Section: Fear Of Compassion For Othersmentioning
confidence: 99%
“…Although compassion has been shown to have positive affects (Gilbert et al 2010), there are some who fear it. This is extremely problematic from an evolutionary standpoint as affiliative emotions help us regulate threats and social isolation (Depue and Morrone-Strupinsky 2005).…”
Section: Fear Of Compassion From Othersmentioning
confidence: 99%
See 1 more Smart Citation